2015
DOI: 10.1159/000438556
|View full text |Cite
|
Sign up to set email alerts
|

MiR-203 Determines Poor Outcome and Suppresses Tumor Growth by Targeting TBK1 in Osteosarcoma

Abstract: Background/Aims: Increasing evidence has shown that miR-203 plays important role in human cancer progression. However, little is known about the function of miR-203 in osteosarcoma (OS). Methods: The expression of miR-203 in OS tissues and cell lines were examined by qRT-PCR. The biological role of miR-20 in OS cell proliferation was examined in vitro and in vivo. The targets of miR-203 were identified by a luciferase reporter gene assay. Results: miR-203 was down regulated in OS tissues and cell lines; decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Evidence shows that miR-203 acts an important role in the regulation of tumor proliferation, migration and invasion. Some studies indicate that miR-203 overexpression suppresses cell growth and metastasis via targeting different genes in different tumor tissues, such as targeting TBK1 in Osteosarcoma [ 28 ], ADAM9 and long non-coding RNA HULC in hepatocellular carcinoma [ 29 ], Rap1A in prostate cancer [ 30 ], Ran and miR-21 in esophageal cancer [ 31 ]. However, few studies show that miR-203 may function as the carcinogenic factor via enhancing cell proliferation, migration and invasion by degrading SIK1 in pancreatic cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that miR-203 acts an important role in the regulation of tumor proliferation, migration and invasion. Some studies indicate that miR-203 overexpression suppresses cell growth and metastasis via targeting different genes in different tumor tissues, such as targeting TBK1 in Osteosarcoma [ 28 ], ADAM9 and long non-coding RNA HULC in hepatocellular carcinoma [ 29 ], Rap1A in prostate cancer [ 30 ], Ran and miR-21 in esophageal cancer [ 31 ]. However, few studies show that miR-203 may function as the carcinogenic factor via enhancing cell proliferation, migration and invasion by degrading SIK1 in pancreatic cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-203 can strongly decrease the fraction of side population cells and colony formation by targeting Bmi-1 in esophageal cancer and leukemia stem cell [5, 52]. In osteosarcoma, inhibition of miR-203 stimulated cell growth by targeting TBK1 and RAB22A [53, 54]. Therefore, miR-203 is involved in tumor cell differentiation, proliferation and metastasis, and is thought to be a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-203 is located in a frequently lost chromosomal region in T cell malignancies [ 17 ], and its expression is downregulated in tumors [ 9 12 , 18 , 19 ]. Previous study has demonstrated miR-203 was a putative tumor suppressor gene in several tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Liu et al reported miR-203 was down regulated in osteosarcoma tissues and cell lines. Decreased miR-203 was associated with a poor prognosis in osteosarcoma patients [ 18 ]. Inhibition of miR-203 stimulated osteosarcoma cell growth by targeting TBK1, proliferation and RAB22A [ 18 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%